Improving Environmental Literacy and Creative Thinking Skills Through Earth and Space Science Integrated Eco-Pedagogy (ESS-EcoP) Module - Nurasyah Dewi Napitupulu; Miftah; Muhammad Zaky; Siddik; Amelia Septianti; Regina Chalista Agata Talokon (Jurnal Penelitian Pendidikan IPA, 2025)
Eco-pedagogy is an educational approach that places emphasis on the relationship between humans and the natural world, and encourages the undertaking of practical actions for the benefit of environmental sustainability. The objective of this study is to enhance students' environmental literacy and creative thinking abilities through the Earth and Space Science (ESS) integrated eco-pedagogy (EcoP) modules. This research is development research (R & D) using 4-D model by Thiagarajan. The research subjects were 22 prospective physics teacher students. Data on environmental literacy and creative thinking skills were collected through pre-test and post-test by using the environmental literacy test and creative thinking skills questionnaire. The results demonstrated that the implementation of the validated ESS-EcoP module integrated with eco-pedagogy can markedly enhance 65.05% students' environmental literacy and 55.49% students’ creative thinking skills. This research is anticipated to contribute to the advancement of innovative learning models that can augment students' awareness and concern for the environment.